2003
DOI: 10.1016/s0886-3350(02)01975-2
|View full text |Cite
|
Sign up to set email alerts
|

Transient central retinal artery occlusion after posterior sub-Tenon's anesthesia

Abstract: Two cases of transient central retinal artery occlusion were observed preoperatively after uneventful sub-Tenon's infusion of local anesthetic for cataract surgery and intraocular lens implantation. In these eyes, the retinal circulation reperfused spontaneously before surgery and there were no visual sequelae. A third case was observed in an eye after strabismus surgery with sub-Tenon's anesthesia. The patient was left with profound visual loss in this eye. The cause of this complication is unknown, but possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…1 The incidence of TRAO has not been evaluated in prospective longitudinal case finding studies, although it can be considered as a rare event. 1 We present the largest case series reported of TRAO following phacoemulsification under sub-Tenon's anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 The incidence of TRAO has not been evaluated in prospective longitudinal case finding studies, although it can be considered as a rare event. 1 We present the largest case series reported of TRAO following phacoemulsification under sub-Tenon's anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 A duration of anoxia of 44 h exceeds the retina's maximal survival time, 6 although neuronal cell death may occur within 97 min. 7 TRAO of very short duration may not produce visual symptoms, 1 and further investigation will not be sought. An intermediate duration of occlusion will result in symptoms 1,3,8 despite arteriolar reperfusion proven on FFA; these patients are labelled as having suffered TRAO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors [38][39][40][41] reported retinal and ophthalmic artery occlusion after sub-Tenon's anaesthesia, presumably due to an elevation in ocular and orbital pressure above the mean ophthalmic artery or central retinal artery pressure. This complication may be transient 38,39 or associated with other complications, such as vertical diplopia (consistent with restriction of the inferior rectus muscles), 40 in addition to orbital haemorrhage, orbital cellulitis, and central nervous system depression, 41 Feibel and Guyton 38 suggested other possible mechanisms of retinal damage by sub-Tenon's block, such as pressure on the central retinal artery or posterior ciliary arteries, or ocular vasoconstriction, leading to a decrease in ocular blood flow and a consequent reduction in ocular pulse amplitude and pulsatile blood flow. However, none of our patients sustained serious ocular injury, except for an edematous reaction of the Tenon's capsule and conjunctiva in the injected area.…”
Section: Discussionmentioning
confidence: 99%